Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Is xylem sap calcium responsible for reducing stomatal conductance after soil liming? - Christopher J. Atkinson (Plant and Soil, 2014)

Effects of two contrasting canopy manipulations on growth and water use of London plane (Platanus x acerifolia) trees - Neil A. Hipps; Michael J. Davies; Joel M. Dunn; Howard Griffiths; Christopher J. Atkinson (Plant and Soil, 2014)

Repeated core temperature elevation induces conduit artery adaptation in humans - Howard H. Carter; Angela L. Spence; Ceri L. Atkinson; Christopher J. A. Pugh; Louise H. Naylor; Daniel J. Green (European Journal of Applied Physiology, 2014)

Recombinant monoclonal antibody yield in transgenic tobacco plants is affected by the wounding response via an ethylene dependent mechanism - Sally Hassan; Richard Colgan; Mathew J. Paul; Christopher J. Atkinson; Amy L. Sexton; Craig J. van Dolleweerd; Eli Keshavarz-Moore; Julian K-C. Ma (Transgenic Research, 2012)

Potential mechanisms for achieving agricultural benefits from biochar application to temperate soils: a review - Christopher J. Atkinson; Jean D. Fitzgerald; Neil A. Hipps (Plant and Soil, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Irrigation scheduling and irrigation systems: optimising irrigation efficiency for container ornamental shrubs - Olga M. Grant; Michael J. Davies; Helen Longbottom; Christopher J. Atkinson (Irrigation Science, 2009)

Neurobehavioral effects of human immunodeficiency virus infection among former plasma donors in rural China - Robert K Heaton; Lucette A Cysique; Hua Jin; Chuan Shi; Xin Yu; Scott Letendre; Donald R Franklin; Christopher Ake; Ofilio Vigil; J Hampton Atkinson; Thomas D Marcotte; Igor Grant; et al. (Journal of NeuroVirology, 2008)

Effects of elevated p CO 2 on epilithic and endolithic metabolism of reef carbonates - TRIBOLLET ALINE; M. J. ATKINSON; LANGDON CHRISTOPHER (Global Change Biology, 2006)
We investigated effects of elevated partial pressure of CO 2 ( p CO 2 ) on the metabolism of epilithic and endolithic phototrophic communities that colonized experimental coral blocks. Blocks of the massive coral Porites lobata were exposed to colonization by epilithic and endolithic organisms at an oceanic site in Kaneohe Bay (Hawaii) for 6 months, and then were transported to laboratory tanks. A bubbling system was used to maintain two treatments for 3 months, one at ambient p CO 2 (400 ppm) and the second at elevated p CO 2 (750 ppm). Net photosynthetic rates of epilithic communities in the high p CO 2 treatment, dominated by encrusting coralline algae, decreased by 35% while respiration rates remained constant. In contrast, metabolism of endolithic phototrophs, comprised of cyanobacteria and algae, was not significantly affected by the elevated p CO 2 even though endoliths contributed about 63% to block production.

Drought tolerance of apple rootstocks: Production and partitioning of dry matter - Christopher J. Atkinson; Michaelangelo Policarpo; Anthony D. Webster; Ayzin M. Kuden (Plant and Soil, 1999)